Themes of scientific production of the cuban journal of pharmacy indexed in scopus (1967-2020) - Chung, Sun Ah (2021)
Introduction: The Cuban Journal of Pharmacy celebrated this year its fifty-fourth anniversary, and during all these years it has successfully published more than 1110 works indexed in Scopus bibliographic database until 2020. Objective: Describe the scientific production from the thematic point of view of the Cuban Journal of Pharmacy indexed in Scopus. Methods: A qualitative study was carried out, based on the systematic review of scientific literature published by the Cuban Journal of Pharmacy, available in Scopus. Publications were grouped by thematic areas according to the authors' criteria, based on the keywords presented in the abstracts and the central theme of the article. The thematic areas defined were eight, with eight sub-themes. Conclusions: Since 1967, the Cuban Journal of Pharmacy has strived to promote the development of science and research in its home country, Cuba. However, because of the variety of its articles it is of great value to foreign researchers and students too. The studies presented have been characterized by the diversity of topics related to pharmacology, the use of Cuban medicinal plants for therapeutic purposes and the methodology for better drug’s production and laboratory procedures.